Integrasi Pendekatan Digital dan Pendekatan Partisipatif dalam Meningkatkan Kualitas Layanan PAUD: Sebuah Transformasi Manajemen Keuangan di Lembaga PAUD - Syahrul Munawar; Maulana Ahmad Jailani; Fetty Ernawati (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Early Childhood Education (ECE) plays a fundamental role in shaping the quality of human resources, as this stage represents a critical period for children's cognitive, social-emotional, and moral development; however, financial management in ECE institutions often faces challenges such as limited funding, non-standardized systems, and low transparency, which may affect service quality. This study aims to analyze financial management strategies and examine their effectiveness and efficiency through the integration of digital and participatory approaches in improving ECE service quality. This research employs a library research method by reviewing relevant literature, including books and scientific journal articles, with data analyzed using a qualitative descriptive approach through reduction, categorization, and synthesis. The findings reveal that effective financial management is achieved through integrated managerial functions, supported by digital systems that enhance accuracy, transparency, and efficiency, as well as participatory approaches that strengthen accountability and stakeholder involvement. In conclusion, the integration of strategic, digital, and participatory financial management contributes to more adaptive, transparent, and sustainable governance in ECE institutions.